O Misticismo Judaico e Apocalíptico no Apocalipse de João Capítulos 4 e 5 Ascenção e Viagem Celestial no Cristianismo Primitivo - Dantas, Marcelo Alves (2014)
This dissertation has its purpose on the texts of the book of Revelation chapters 4 and 5. Their source of research belongs to the Jewish Mysticism. This way of examination echoes today in studies of apocalyptic mysticism and the visionary ecstasy relating to the context of Judaism and primitive Christianity, on authors such as Christopher Rowland, Alan Segal, C.R.A. Morray - Jones and John Ashton, John Collins, Adella Collins, Jonas Machado, Paulo A.S. Nogueira, Carol Newsom, David E. Aune, Philip Alexander, Crispin H.T. Fletcher - Louis, Florentino García Martínez among others; but these authors align themselves to the Gershom Scholems initial research results on Jewish Mysticism, and also to the latest developments in this subject. Nogueira mentions that Scholem was who actually used this mysticism to produce the key for heavenly ascent stories present on apocalypses of the last two centuries b.C. and also to the first two centuries a.D. In fact, Scholem was who initiated the Jewish mysticism academic discussion in his book Major Trends in Jewish Myticism in 1941. Strengthening the tradition of these studies are the findings of the Qumran manuscript, such as the Songs of the Sabbath Sacrifice, a thirteen songs composition, also called angelic liturgy, that has contributed to the research development as well as supporting the Scholem arguments. Among the Qumran manuscripts a hymn fragment called 4Q405 brought to the acquaintance the terminology Merkaváh, wherein angels praise the Chariot Throne image mentioned in the first chapter of the book of Ezekiel. It was identified on that the Qumran community syncretism regarding the song of angels with other ideas about their duties, being a common characteristic of Maasseh Merkavah traditions - (Divine Throne / Chariot tasks). Thus, the research follows the presupposed by Rowland that the texts of Revelation 4 and 5 have in their narrative a basic similarity to the liturgy described in the traditions of the first century Judaism apocalyptic mysticism, as well as on Qumran texts, mainly in 4Q405 fragment. According to Nogueira Ezekiel chapter 1 is considered the key to the Judaism mysticism tradition, therefore also being a central element of the Johns Apocalypse, the main visionary of Christianity. The research includes the approach of texts considered the ones that established Ezekiel 1, Isaiah 6, Daniel 7, I Enoch 14, the analysis of the Qumran texts, as the complex of 13 Sabbatical Songs related to worship in the celestial sanctuary. The apocalyptic is thus understood as a kind of mystical literature, whose images reflect the writings that, by means of the visionary ascent to heaven and the contemplation of Gods Throne pull the curtain certain tradition of the 1st. century. Therefore, it can be also interpret the chapters 4 and 5 of Revelation as a mystical text, with similar content to the Jewish apocalyptic texts, and perhaps with a similar type of religious experience.